Tailored-CuO-nanowire decorated with folic acid mediated coupling of the mitochondrial-ROS generation and miR425-PTEN axis in furnishing potent anti-cancer activity in human triple negative breast carcinoma cells. (January 2016) - Ahir, Manisha; Bhattacharya, Saurav; Karmakar, Soumendu; Mukhopadhyay, Ayan; Mukherjee, Sudeshna; Ghosh, Swatilekha; Chattopadhyay, Sreya; Patra, Prasun; Adhikary, Arghya
Abstract: Metal oxide nanoparticles are the forthcoming anti-tumor therapeutics and provide a versatile platform in the development of therapeutic approaches for drug-resistant cancers such as triple negative breast cancer (TNBC). Copper oxide nanoparticles have been characterized as anti-cancer agents but its toxicity has been a matter of concern. Herein, we have developed a targeted CuO Nanowire fabricated with Folic acid (CuO-Nw-FA) that enables enhanced cellular uptake in TNBC cells without imparting significant toxicity in normal cellular system. In the present study, we enumerated that CuO-Nw-FA caused mitochondrial-dependent apoptosis in MDAMB-231 cells. Furthermore, CuO-Nw-FA mediated cytosolic retardation of NF-κB favoured inactivation of miR-425 and henceforth activated PTEN to induce apoptosis in TNBC cells. Simultaneously, CuO-Nw-FA also restricted the in-vitro cell migration through the miR-425/PTEN axis via pFAK. Studies extended to ex-ovo and in-vivo mice models further validated the efficacy of CuO-Nw-FA. Additionally, the accumulations of nanoparticles in tumor as well as different organs in mice were examined by in-vivo biodistribution and ex-vivo optical imaging studies. Thus our results cumulatively propose that CuO-Nw-FA cross-talks two distinct signalling pathways to induce apoptosis and retard migration in TNBC cells and raises the possibility for the use of CuO-Nw-FA as a potent anti-tumor agent.